2010
DOI: 10.1213/ane.0b013e3181af8015
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Anesthetic Properties: The Effects of Isoflurane on Brain Cell Death, Neurogenesis, and Long-Term Neurocognitive Function

Abstract: Anesthetic drugs cause brain cell death and long-term neurocognitive dysfunction in neonatal rats. Recently, human data also suggest that anesthesia early in life may cause cognitive impairment. The connection between cell death and neurocognitive decline is uncertain. It is conceivable that mechanisms other than brain cell death contribute to neurocognitive outcome of neonatal anesthesia. In a series of experiments, we demonstrate that isoflurane exposure causes significant hypercarbia in postnatal day 7 rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 40 publications
1
50
1
1
Order By: Relevance
“…Also, the MAP and heart rates of monkeys in the present study were maintained in the normal ranges during the entire study of each session (although a decreasing tendency in MAP or heart rate was seen after 2 h of isoflurane exposure) (Fig. 2), in agreement with those seen in a previous study in rats under 1 minimum alveolar concentration (MAC) isoflurane for 4 h (Stratmann et al, 2010) and dogs (1.4% isoflurane from 2 to 6 h) (Brian et al, 1990).…”
Section: Long-duration Effect Of Isoflurane On Cbfsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the MAP and heart rates of monkeys in the present study were maintained in the normal ranges during the entire study of each session (although a decreasing tendency in MAP or heart rate was seen after 2 h of isoflurane exposure) (Fig. 2), in agreement with those seen in a previous study in rats under 1 minimum alveolar concentration (MAC) isoflurane for 4 h (Stratmann et al, 2010) and dogs (1.4% isoflurane from 2 to 6 h) (Brian et al, 1990).…”
Section: Long-duration Effect Of Isoflurane On Cbfsupporting
confidence: 92%
“…Meanwhile, it has been reported that an increased risk for neurobehavioral disturbances correlates positively with the duration of anesthesia exposure (Block et al, 2012;Wilder et al, 2009). Animal studies have further demonstrated that spatial memory was impaired for 2 weeks after long-duration administration of isoflurane in aged rats (Culley et al, 2004) and isoflurane might cause brain cell death, neurocognitive decline in immature rats (Stratmann et al, 2010).…”
mentioning
confidence: 99%
“…Stratmann et al (2010) showed that in P7 rat brain, cell loss likely reflects severity of the treatment and cannot be causally linked to subsequent cognitive dysfunctions. Also, it needs to be determined if the absence of neuronal cell death does mean that surviving neurons are not impacted by anesthesia and function properly.…”
Section: Neurotox Resmentioning
confidence: 99%
“…136 Anesthesia induced neurodegeneration have also been reported to cause persistent hippocampal dysfunction and cognitive dysfunction. 137 Volatile anesthetics mainly isoflurane, as researched on animal, was found to produce AD like pathology like Ab oligomerization and cytotoxicity and aberrant t phosphorylation and aggregation. IV propofol may also produce same AD like pathology.…”
Section: Anesthetic Agentsmentioning
confidence: 99%